Pancasila Philosophy As A Basis For The Implementation Of Restorative Justice In The Settlement Of Environmental Criminal Cases - Hawina Romli; Rahayu Subekti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to examine the potential of restorative justice to resolve environmental criminal violations from the perspective of Pancasila philosophy, exploring relevant concepts so that they can be applied in the process of resolving environmental criminal cases. The type of research used is normative or doctrinal legal research. Normative research is research that usually uses documents as sources of legal materials such as laws and regulations, court decisions, legal theories, and opinions of legal scholars. The restorative justice approach in resolving environmental criminal cases can only be applied to formal offenses in Article 100. The concept of Restorative Justice is in accordance with the 4th Principle, namely deliberation which contains the principles of conferencing, search solutions, reconciliation, repair and circles (mutual support).